Signature Codes in Visible Light Positioning - Jin, Jianli; Feng, Lifang; Wang, Jianping; Chen, Danyang; Lu, Huimin (IEEE wireless communications, 2021)
With the explosive development of the Internet of Things (IoT), massive equipments are involved in the indoor environment with the demand of precise localization to provide intelligent interconnection. The visible light positioning (VLP) system, with the light emitting diode (LED) and the photo-diode (PD) or image sensor as the transceiver, has attracted a lot of attention due to low cost, high accuracy, energy efficiency, electromagnetic interference free, safety, and so on. In this article, we address the architecture and multiplexing methods of the VLP systems, together with their influence in positioning. From the engineering's point of view, we introduce a novel signature code with reduced complexity and computation. Performing the coding and decoding scheme, the received signal strengths (RSSs) from different LEDs can be decomposed. Based on these RSSs, an adaptive positioning mechanism is first considered following the analysis of merits of the common positioning algorithms, which is verified with optimal positioning performance. It can be concluded that the proposed VLP system has great potential to fit well for a large scene with massive IoT devices.